PENINGKATAN PROSES PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MODEL ACTIVE LEARNING TIPE TEAM QUIZ DI KELAS V SD - Nur Elisa Putri; Taufina Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this research is to describe the improvement of the integrated thematic learning process using the Inquiry learning model in class V SDN 09 Belakang Balok Kota Bukitinggi. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were teachers and 28 students. The results showed the value of planning the first cycle learning 82.94% and increasing the second cycle 93.18%. The observations of aspects of the first cycle teacher 82.25% and 95.87% increased the second cycle. The results of observations of aspects of students in the first cycle 79.17% and increase in the second cycle 93.6%. It can be concluded in the study that learning using team quiz of active learning model can improve the learning process in elementary schools.